equação do 1 grau da propriedade distributiva 5+2(3-2×)=6×+1
Soluções para a tarefa
Respondido por
1
Resposta: 1
5 + 2(3-2x) = 6x + 1
5 + 6 - 4x = 6x + 1
-4x - 6x = 1 - 5 - 6
-10x = -10 . (-1)
x = 10/10
x = 1
5 + 2(3-2x) = 6x + 1
5 + 6 - 4x = 6x + 1
-4x - 6x = 1 - 5 - 6
-10x = -10 . (-1)
x = 10/10
x = 1
vany8857:
obrigado ❤
Respondido por
1
Resposta:
x = -6
Explicação passo-a-passo:
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Português,
10 meses atrás
História,
1 ano atrás
Português,
1 ano atrás
Filosofia,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás